Characteristics of delivery pressure in the axial piston pump with combination of variable displacement and variable speed. (August 2015) - Huang, Jiahai; Yan, Zheng; Quan, Long; Lan, Yuan; Gao, Youshan
In recent years, a trend toward the combination of variable displacement and speed-variable pump drive is becoming apparent. Combination of variable displacement and speed-variable pump drive has been revealed to be more efficient than speed-variable pump drive or variable displacement pump drive. However, few research works have dealt with the pumping performance of combination of variable displacement and speed-variable pump. This study aims to investigate the characteristics of pressure pulsations of combination of variable displacement and speed-variable pump. A simulation model is developed by means of software package ITI-SimulationX ® . The model is used to predict the pressure pulsations under different operating conditions. Experiments are also carried out to verify theoretical results. From these results, it can be drawn that the pumping dynamics of combination of variable displacement and speed-variable pump is not the best in the view of pressure pulsation, and it is slightly inferior to that of variable displacement pump drive. For required delivery volumetric flow and load pressure, delivery pressure pulsations' amplitude of combination of variable displacement and speed-variable pump slightly increases with an increase in swash plate angle and adapted rotational speed. However, test results also show that lower rotational speed and adapted swash plate angle working condition can effectively reduce total noise level of the system. Consequently, lower rotational speed and higher swash plate angle working condition are suggested for the design of combination of variable displacement and speed-variable pump drive controller.